Mutations of the Birt–Hogg–Dubé gene in patients with multiple lung cysts and recurrent pneumothorax. Issue 9 (11th May 2007) - Gunji, Yoko; Akiyoshi, Taeko; Sato, Teruhiko; Kurihara, Masatoshi; Tominaga, Shigeru; Takahashi, Kazuhisa; Seyama, Kuniaki
Abstract : Rationale: Birt – Hogg – Dubé (BHD) syndrome, a rare inherited autosomal genodermatosis first recognised in 1977, is characterised by fibrofolliculomas of the skin, an increased risk of renal tumours and multiple lung cysts with spontaneous pneumothorax. The BHD gene, a tumour suppressor gene located at chromosome 17p11.2, has recently been shown to be defective. Recent genetic studies revealed that clinical pictures of the disease may be variable and may not always present the full expression of the phenotypes. Objectives: We hypothesised that mutations of the BHD gene are responsible for patients who have multiple lung cysts of which the underlying causes have not yet been elucidated. Methods: We studied eight patients with lung cysts, without skin and renal disease; seven of these patients have a history of spontaneous pneumothorax and five have a family history of pneumothorax. The BHD gene was examined using PCR, denaturing high-performance liquid chromatography and direct sequencing. Main results: We found that five of the eight patients had a BHD germline mutation. All mutations were unique and four of them were novel, including three different deletions or insertions detected in exons 6, 12 and 13, respectively and one splice acceptor site mutation in intron 5 resulting in an in-frame deletion of exon 6. Conclusions: We found that germline mutations of the BHD gene are involved in some patients with multiple lung cysts and pneumothorax. Pulmonologists should be aware that BHD syndrome can occur as an isolated phenotype with pulmonary involvement.